A Model for Out-of-Hospital Multispecialty Emergency Medicine: Accomplishments and Challenges. (October 2018) - Theocharis, George; Kechagias, Konstantinos S; Oikonomou, Michael; Chorepsima, Stamatia; Rodis, Dionisis; Salpigktis, Ioannis; Falagas, Matthew E
Home care has been traditionally considered as an important type of medical service. "SOS Doctors" is a Greek organization providing out-of-hospital multispecialty emergency medicine services the past 25 years. Its services mainly meet the demands of the elderly and the nonambulatory patients. The decreased number of hospitalizations, hospital-related infections, and need for patient transportation are the main advantages of a model for out-of-hospital multispecialty emergency medicine. However, the time consumed by the doctor related to transportation is a drawback of medical house calls. Despite the challenges, medical house calls are a useful part of health services in the modern health care system.